Nanometer structures theory, modeling, and simulation - Lakhtakia, A. 1957- (SPIE Press, 2004)
This volume is a researcher's reference handbook to the many aspects of nanometer structures. Although intended as a source for the serious researcher, novices will find a great deal of interesting content. The theories covered include nanostructured thin films, photonic bandgap structures, quantum dots, carbon nanotubes, atomistic techniques, nanomechanics, nanofluidics, and quantum information processing. Modeling and simulation research on these topics have now reached a stage of maturity to merit inclusion as well.
Keywords: Nanotechnology -- Handbooks, manuals, etc.; elektronické knihy; electronic books